2020
DOI: 10.15294/maj.v9i1.34585
|View full text |Cite
|
Sign up to set email alerts
|

Board Interlocking and Firm Performance: Evidence from Indonesia

Abstract: This study aims to determine the relationships of board interlocking and firm performance as measured by Return on Assets (ROA). This research method uses a quantitative approach with research objects of all companies listed on the Indonesia Stock Exchange period 2008-2017. The sample selection method uses a purposive sampling. The sample used was 4450 observation. Data analysis methods used are descriptive analysis and dummy variable regression Analysis of Covariance (ANCOVA). The result showed that the avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…These results prove that the hypothesis which states the place influences customer satisfaction can be accepted. This research is in line with research conducted by (Bailia, et al 2014), (Pertiwi, Yulianto, & Sunarti, 2016), (Sari et al, 2018), (Abbas, 2015), and (Wulandari & Mudiantono, 2013) where the results show that place has a significant effect on customer satisfaction. Based on observations, Solata Café is easily accessible so it becomes one of the main choices for consumers to hang out while eating and drinking.…”
Section: Research Findingsupporting
confidence: 92%
“…These results prove that the hypothesis which states the place influences customer satisfaction can be accepted. This research is in line with research conducted by (Bailia, et al 2014), (Pertiwi, Yulianto, & Sunarti, 2016), (Sari et al, 2018), (Abbas, 2015), and (Wulandari & Mudiantono, 2013) where the results show that place has a significant effect on customer satisfaction. Based on observations, Solata Café is easily accessible so it becomes one of the main choices for consumers to hang out while eating and drinking.…”
Section: Research Findingsupporting
confidence: 92%
“…In Indonesia, Pertiwi and Yulianto (2020) found support for the resource dependence theory, with interlocked firms having higher profits.…”
Section: Southeast Asian Studiesmentioning
confidence: 89%
“…Ong et al (2003), on the other hand, investigated interlocking relationships in Singapore and documented a positive correlation between interlocking and corporate performance measured by return on assets (ROA), return on equity (ROE), and return on sales (ROS). In Indonesia, Pertiwi and Yulianto (2020) showed that the average performance of companies (based on their ROA) with interlocking directors is higher than those without. Additionally, Dayanandan et al (2019) concluded that, in India, the lack of caste diversity in boards, CEOs, and interlocks is associated with lower firm value.…”
Section: Hypothesis Developmentmentioning
confidence: 99%